Performative Ethics in the Trump Era: A Postmodern Examination. (3rd September 2019) - Santis, Esteban Leonardo; Zavattaro, Staci M.
Abstract : As public administration continues its postmodern turn, there is a need to reexamine administrative ethics. In this article, the concept of "performative ethics" is introduced as a counter to ethics based solely on bureaucratic codes, professional obligations, and democratic ideals. Overall, this article is theoretical in that it is meant to offer an interpretation of today's administrative ethics from a postmodern perspective and find ways to make sense of it all. Additionally, President Trump's use of "Make America Great Again" (MAGA), "fake news, " and false or misleading claims are discussed in a case study that details the applicability and power of performative ethics. Conclusively, the article offers some suggestions for administrators and citizens thinking about postmodernity and counter-narratives.